Examining preservice teacher content and pedagogical content knowledge needed to teach reading in elementary school. (1st July 2015) - Clark, Sarah K.; Helfrich, Sara R.; Hatch, Lance
Abstract : Recently, increased attention has been placed on the importance of having knowledgeable and skilled teachers in order to influence reading achievement. Yet many international reports suggest that large numbers of children are not learning to read. How can we better prepare teachers with the necessary knowledge to teach reading? The current study examined the reading instructional knowledge of elementary education preservice teachers ( N  = 87) from two teacher education programmes. Programme A required five reading methods courses and Programme B required two methods courses. Findings indicate that the preservice teachers presented fairly robust levels of knowledge in the areas of phonological awareness, phonics, comprehension and vocabulary. However, we found statistically significant differences in knowledge based on the programme attended and the number of courses completed. Suggestions for improving reading teacher education are provided.